2013
DOI: 10.1007/s00381-012-2015-2
|View full text |Cite
|
Sign up to set email alerts
|

Rathke’s pouch remnant and its regression process in the prenatal period

Abstract: Rathke's pouch may be closed by ossification of the sphenoid, but increased cell proliferation and/or large amounts of degenerated veins may provide a structure resistant to the mechanical pressure caused by ossification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…The medial ossification centers of the postsphenoid, which later form the sella turcica, usually unite to form a single ossification center, but such unity may not happen as soon as the individual centers form, which may, in turn, cause the variable timing in the disappearance of the craniopharyngeal canal, not restricted to a specific gestational age. 10,14,16,27 Imaging findings for postsphenoid ossification have been discussed in the literature only as hyperattenuation on CT and low intensity on T2-weighted images, 16 and the characteristic appearance of postsphenoid ossification on T1WI as shown in this study has not been previously reported, to our knowledge, due to a lack of fetal MR imaging data on intrasphenoid lesions. Calcification usually appears as a low signal on both T1WI and T2WI, but calcium salts interact with water protons in the process of ossification, in turn slowing the precession to near the Larmor frequency and potentially leading to short T1 relaxation times.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The medial ossification centers of the postsphenoid, which later form the sella turcica, usually unite to form a single ossification center, but such unity may not happen as soon as the individual centers form, which may, in turn, cause the variable timing in the disappearance of the craniopharyngeal canal, not restricted to a specific gestational age. 10,14,16,27 Imaging findings for postsphenoid ossification have been discussed in the literature only as hyperattenuation on CT and low intensity on T2-weighted images, 16 and the characteristic appearance of postsphenoid ossification on T1WI as shown in this study has not been previously reported, to our knowledge, due to a lack of fetal MR imaging data on intrasphenoid lesions. Calcification usually appears as a low signal on both T1WI and T2WI, but calcium salts interact with water protons in the process of ossification, in turn slowing the precession to near the Larmor frequency and potentially leading to short T1 relaxation times.…”
Section: Discussioncontrasting
confidence: 48%
“…Defects in this fusion will lead to nonobliteration of the adenohypophyseal stalk connecting the Rathke pouch to the stomodeum, creating a patent canal connecting the sella turcica and pharynx, known as the craniopharyngeal canal. [13][14][15] A patent craniopharyngeal canal with a small diameter can be observed in healthy patients. 8 We will refer to the ossification around the Rathke pouch as "postsphenoid ossification" for simplicity in this study.…”
mentioning
confidence: 98%
“…If it fails to regress and be obliterated, the cleft may dilate and be filled with fluid or mucus, resulting in a RCC. This histological and anatomic basis of RCC formation also explains why most RCCs are located between the anterior and posterior lobes of the pituitary (10)(11)(12). Some authors have suggested that the cyst could appear anywhere along the usual migration path of Rathke's pouch (12,13).…”
Section: Discussionmentioning
confidence: 96%
“…This histological and anatomic basis of RCC formation also explains why most RCCs are located between the anterior and posterior lobes of the pituitary (10)(11)(12). Some authors have suggested that the cyst could appear anywhere along the usual migration path of Rathke's pouch (12,13). Second, the adenohypophysis develops closely with the neurohypophysis, especially the median parts (the pars intermedia and pars tuberalis), along with the infundibular stem.…”
Section: Discussionmentioning
confidence: 98%
“…Unlike Rathkes cleft, at 6 weeks of age, the pouch lengthens to form a narrow stalk. By the seventh week of age, the sphenoid base develops, obliterating the stalk through the transition from cartilage to cortication of the sphenoid body [ 3 ]. Persistence of the stalk occurs when there is abnormal fusion of the pre-sphenoidal and post-sphenoidal cartilages.…”
Section: Discussionmentioning
confidence: 99%